Minimal influence of estrous cycle on studies of female mouse behaviors - Zeng, Pei-Yun; Tsai, Ya-Hsuan; Lee, Chih-Lin; Ma, Yu-Kai; Kuo, Tsung-Han (Frontiers in Molecular Neuroscience, 2023)
Sex bias has been an issue in many biomedical fields, especially in neuroscience. In rodent research, many scientists only focused on male animals due to the belief that female estrous cycle gives rise to unacceptable, high levels of variance in the experiments. However, even though female sexual behaviors are well known to be regulated by estrous cycle, which effects on other non-sexual behaviors were not always consistent in previous reports. Recent reviews analyzing published literature even suggested that there is no evidence for larger variation in female than male in several phenotypes. To further investigate the influence of estrous cycle on female variability, in this study, we compared multiple behaviors between females in estrus and diestrus stages in four different mouse strains, C57BL/6, BALB/c, C3H, and DBA/2. We performed the open field test, forced swimming test, and resident-intruder assay to assess anxiety-, depression-like behaviors, as well as social interaction respectively but found no significant difference in most behavioral parameters between females in these two stages. On the other hand, the differences in behaviors among certain strains are relatively consistent in both stages, suggesting a very minimal effect of estrous cycle for detecting the behavioral difference. Last, we compared the behavioral variation between male and female and found very similar variations in most behaviors between the two sexes. Together, our data suggested no solid evidence that female behaviors are affected by estrous cycle, and most behaviors are equally variable between the two sexes. Female mice, therefore, have no reason to be excluded in future behavioral research.